Sporadic Low Salinity Signals in the Oceanic Mixed Layer Observed by the Kuroshio Extension Observatory Buoy - Kameyama, Kohei; Kanno, Yuki; Ohishi, Shun; Tomita, Hiroyuki; Fukutomi, Yoshiki; Aiki, Hidenori (Frontiers in Climate, 2022)
The hourly measurements of air-sea interaction parameters made at the Kuroshio Extension Observatory (KEO) buoy since 2004 have produced an extensive dataset that can be used to understand the dynamics of the oceanic mixed-layer under extreme weather conditions. Our analysis of the KEO-buoy measurements reveals the presence of sporadic low-salinity signals (SLSSs) with duration of 1-2 days in the mixed-layer when, for example, tropical cyclones (TCs) approach. Here SLSS events are identified within the buoy data by using a flag which is set to unity when the value of normalized salinity falls below -1 (minus one). Application of this definition to the hourly time series of salinity measured at 10m depth by the KEO buoy has allowed us to identify 244 SLSS events over the 11-year analysis period. Both winter (January-March) and spring (April-June) seasons show a peak in the composite time series of wind velocity subdiurnal variation (WVDV) near the start time of SLSS events. SLSS events can be terminated by the entrainment of saltier subsurface water parcels to the mixed-layer in response to storms. The discovery of the WVDV peaks following SLSS commencement is the reason the present study has adopted a time scale of 1-day wind velocity analysis. This temporal resolution has enabled us to identify a TC-related delay in the development of the WVDV peaks, which may represent a fundamental characteristic of the influence of TCs on these events.